Review on Pharmacognostic, Phytochemical and Pharmacological Characteristics of Medicinal Plants which can be used to Design a Novel Ayurvedic Formulation to Treat Hypertension in Multidimensional Approaches - Maurya, Rahul; Boini, Thirupataiah; Misro, Lakshminarayana; Radhakrishnan, Thulasi; Singh, Ravindra (Current Hypertension Reviews, 2023)
Background: Hypertension is a cardiovascular disorder that is an incurable clinical condition. It requires lifelong therapy for its management along with long terms application of synthetic drugs associated with severe toxicity in multiple organs. However, the therapeutic application of herbal medicines to treat hypertension has gained considerable attention. The limitations and hurdles associated with conventional plant extract medications are their safety, efficacy, dose, and unknown biological activity. Objective: In the modern era, the active phytoconstituent-based formulation has come into trend. Various extraction techniques have been reported to extract and isolate active phytoconstituents. Pharmacognostic, physiochemical, phytochemical, and quantitative analytical methods were developed for their qualitative and quantitative analysis. The passage of time and changes in lifestyle also modulate the variable cause of hypertension. Single-drug-based approach therapy cannot efficiently control the cause of hypertension. Designing a potent herbal formulation with different active constituents and modes of action against hypertension is necessary to effectively manage hypertension. Methods: This review comprises a selection of three different plants, Boerhavia diffusa, Rauwolfia Serpentina, and Elaeocarpus ganitrus exhibiting antihypertension activity. Results: The objective behind selecting individual plants is their active constituents which have different mechanisms of action for the treatment of hypertension. This review comprises the various extraction methods of the active phytoconstituents and pharmacognostic, physiochemical, phytochemical, and quantitative analysis parameters, respectively. It also lists active phytoconstituents present in plants and the different pharmacological modes of action. Selected plant extracts have different antihypertensive mechanisms. Extract of Boerhavia diffusa consisting of Liriodendron & Syringaresnol mono β-D-Glucosidase exhibit Ca2+ channel antagonistic activity; where Reserpine is a phytoconstituent of Rauwolfia serpentina, which depletes catecholamine, Ajmalin shows an antiarrhythmic effect by blocking the sodium channel and the aqueous extract of E. ganitrus seeds reduces mean arterial blood pressure by inhibiting the ACE enzyme. Conclusion: It has been revealed that poly-herbal formulation of respective phytoconstituent can be used as potent antihypertensive medicine to treat hypertension effectively.
Keywords: hypertension activity